Development Of Biology Learning Tools To Improve Communication Skills Reviewed From Humanistic Philosophy - Dian Noer Asyari; Siti Masito; Mochamad Nursalim (FALASIFA : Jurnal Studi Keislaman, 2022)
This research is a developmental research because it develops learning tools to improve students' communication skills in terms of humanistic philosophy. The aim of this study is to create practicable learning instruments for training communication skills in the sense of a humanistic philosophy according to the criteria of validity, practicability and effectiveness. The development of learning devices was based on the four-D model. Research design using a pretest-posttest design with a group. Several insights were gained based on research data: the validity of learning tools developed in good categories; the readability of the developed student textbooks is appropriate for learning; the implementation of the RPP is well categorized; the dominant student activities are communicating information/opinions, asking questions and making presentations with a share of 18.88%; The obstacles encountered when using learning tools are that students are unfamiliar with communication skills, making some students less active participants in the learning process. Students respond positively to the learning process; Guided discovery learning can train students' communication skills; and student learning outcomes are 100% complete after participating in the teaching and learning process. The conclusion of this study is that guided discovery learning tools are feasible (valid, practical and effective) that are used to train students' communication skills.